Hippocampus-sparing volume-modulated arc therapy in patients with World Health Organization grade II glioma: a feasibility study - Xie, Renxian; Huang, Hongxin; Cai, Qingxin; Lu, Jiayang; Chen, Tong; Xie, Keyan; Chen, Jianzhou; Chen, Chuangzhen (Frontiers in Oncology, 2025)
BackgroundRadiotherapy can improve the survival rates of patients with glioma; meanwhile, impaired cognitive functions have been brought to the forefront with the offending organ, the radiosensitive hippocampus. This study aimed to assess the feasibility of hippocampus-sparing volumetric-modulated arc therapy (HS VMAT) in patients with World Health Organization (WHO) grade II glioma.MethodsHS VMAT plans and non-hippocampus-sparing volumetric-modulated arc therapy (NHS VMAT) plans were generated using a computed tomography (CT) dataset of 10 patients who underwent postoperative radiotherapy. The dose volume histogram (DVH), homogeneity index (HI), conformity index (CI), and irradiated dose of the hippocampus and other organs at risk (OARs) were analyzed.ResultsNo significant differences were observed in HI and CI between the two plans. Regarding the protection of OARs, HS VMAT plans were equally capable and even lowered the radiation dosages to the brainstem (35.56 vs. 41.74 Gy, p = 0.017) and spinal cord (1.34 vs. 1.43 Gy, p = 0.006). Notably, HS VMAT plans markedly decreased doses to the ipsilateral hippocampus and the contralateral hippocampus, demonstrating its efficacy in hippocampal dose reduction.ConclusionThe HS VMAT plan can be used to efficiently lower the dosage delivered to the hippocampus and may, to some extent, help lessen the risk of cognitive damage. The encouraging results of our study need to be further validated by clinical trials to confirm the benefits of the HS VMAT plans in preserving cognitive functions in patients with glioma.